SYNTHESIS OF COBALT FERRITE (CoFe2O4) NANOPARTICLES BY CO-PRECIPITATION ROUTE - Maaz, K.; Mashiatullah, A.; Qureshi, R. M.; Qazi, N. K.; Mumtaz, A. (The Nucleus, 2020)
Cobalt ferrite (CoFe2O4) nanoparticles have been synthesized by co-precipitation route in the size range 15-25 nm. The X-ray diffractometer (XRD) and Transmission Electron Microscopy (TEM) analyses of the samples confirmed the formation of single phase cobalt ferrite (CoFe2O4) nanoparticles. The size of the particles was studied as a function of annealing temperature and annealing time. It was found that the size of nanoparticles increases linearly with annealing temperature and time due to the coalescence process. Magnetic characterization of samples at room temperature includes DC magnetization hysteresis loops (M-H loops), coercivity (HC) and saturation magnetization (MS), confirmed the formation of core shell structure of CoFe2O4 nanoparticles. Relatively large coercivity at room temperature compared to micro (bulk) CoFe2O4 revealed that Co+2 ions have large effective anisotropy constant (Keff) and strong magnetocrystalline anisotropy in nano-range. Moderate magnetization was observed due to the inert or canted spin layer at the surface of these nanoparticles which prevents the core spins to align along the field direction.